A Total Cost Analysis Model of Construction Logistics Solutions Comparing Direct Delivery and Delivery via a Construction Logistics Center at JM - OSSIANSSON, FILIP; ÅSTRÖM, ELIN (My University, 2021)
The construction industry has challenges in increasing productivity and at the same time keeping production costs down in comparison to other industries. The construction industry also entails a high environmental footprint due to choices of materials and the many materials deliveries necessary for building completion. Rearrangements of construction logistics and implementing supply chain management (SCM) provide possible solutions to these issues. As part of gaining control of the supply chain and reducing the number of deliveries to the site, Construction Logistics Centers (CLCs) are increasingly being used. The aim of this study is to develop a total cost analysis (TCA) model to evaluate two logistics processes of materials delivery to construction site: Direct Delivery or Delivery via a CLC. A reference project at the Swedish construction company JM provides data to the TCA model. The TCA model examines costs in relation to logistics activities from the point of materials leaving the supplier to being placed at the assembly area at the site. The cost data in the TCA are gathered from JM’s framework agreements with suppliers and the CLC-operator. The activities identified in each logistics process are gathered from observations as well as the framework agreements and information from involved parties. The study contributes with a TCA model for different logistics solutions and batch sizes where the TCA itself provides insights of how logistics operations are organized and the costs they entail. The study shows that JM through the implementation of a CLC and the subsidiary JM Supply (responsible for on-site logistics) has taken successive steps towards more efficient SCM. The study contributes to the understanding of the effects of implementing a CLC. The results from the TCA model shows that due to the present supplier agreements and logic of batch sizes, the most cost advantageous logistics solution at JM is the direct delivery to site. However, it should be noted that costs differ significantly in relation to various material types. The TCA model also illustrates that the number of transportations to site decreases with the implementation of a CLC, which is considered a benefit. Thus, to reach the full potential of a CLC solution, JM needs to align purchasing, production, and logistics processes further by taking a holistic perspective of value creation. The research results support JM’s future decision making about the design of their construction logistics solutions as to increase productivity and improve market competitiveness.
Keywords: Construction Logistics; Construction Logistics Centers; Total Cost Analysis; Construction Supply Chain Management; Lean Construction; Logistics Cost Management